Cartridge-Based Thromboelastography Can Be Used to Monitor and Quantify the Activity of Unfractionated and Low-Molecular-Weight Heparins - Dias, João D.; Lopez-Espina, Carlos G.; Panigada, Mauro; Dalton, Heidi J.; Hartmann, Jan; Achneck, Hardean E. (TH Open, 2019)
Thromboelastography is increasingly utilized in the management of bleeding and thrombotic complications where heparin management remains a cornerstone. This study assessed the feasibility of the cartridge-based TEG® 6s system (Haemonetics Corp., Braintree, Massachusetts, United States) to monitor and quantify the effect of unfractionated and low-molecular-weight heparin (UFH and LMWH). Blood samples from healthy donors were spiked with UFH (n = 23; 0–1.0 IU/mL) or LMWH (enoxaparin; n = 22; 0–1.5 IU/mL). Functional fibrinogen maximum amplitude (CFF.MA), RapidTEG activated clotting time (CRT.ACT), and kaolin and kaolin with heparinase reaction time (CK.R and CKH.R) were evaluated for their correlation with heparin concentrations, as well as the combination parameters ΔCK.R − CKH.R, ratio CK.R/CKH.R, and ratio CKH.R/CK.R. Nonlinear mixed-effect modelling was used to study the relationship between concentrations and parameters, and Bayesian classification modelling for the prediction of therapeutic ranges. CK.R and CRT.ACT strongly correlated with the activity of LMWH and UFH (p < 0.001). Using combination parameters, heparin activity could be accurately quantified in the range of 0.05 to 0.8 IU/mL for UFH and 0.1 to 1.5 IU/mL for LMWH. CRT.ACT was able to quantify heparin activity at higher concentrations but was only different from the reference range (p < 0.05) at >0.5 IU/mL for UFH and >1.5 IU/mL for LMWH. Combination parameters classified blood samples into subtherapeutic, therapeutic, and supratherapeutic heparin ranges, with an accuracy of >90% for UFH, and >78% for LMWH. This study suggests that TEG 6s can effectively monitor and quantify heparin activity for LMWH and UFH. Additionally, combination parameters can be used to classify blood samples into therapeutic ranges based on heparin activity.
Keywords: thromboelastography; point-of-care diagnostic system; low-molecular-weight heparin; heparin